REGIONAL DISPROPORTIONS OF PENSION SECURITY IN UKRAINE - KRUPA, Oleksander (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The modern context of regional development in Ukraine is shaped by long-term, unchanged socio-economic characteristics, which collectively cause only the aggravation of interregional and internal regional economic contradictions and do not contribute to strengthening the economic space within the country. The problem of disparities in regional development in Ukraine is particularly relevant in the context of the need to ensure the social security of the country as a whole. Thus, the uneven level of social security of the population, and especially its pension security, contributes to the deepening of regional differentiations in terms of population income indicators, deepens the problem of poverty of the elderly and, as a result, stimulates the development of negative social processes in certain territories.The purpose of the study consists in the analysis of the key indicators of the pension security by regions, the implementation of regional ranking and the characteristics of the key disparities between the regions in order to understand the ways and directions to improving pensions in Ukraine.In the article analyzed the main indicators of pension security in Ukraine in the context of regional development. The regions of Ukraine were ranked according to individual indicators of pension security with distinguishing four main groups. Identified certain disparities in regional pension security and substantiated the reasons and consequences of their existence. Grounded the problematic aspects of current pensions in Ukraine in the context of regional differences in the levels of pension security.
Keywords: pension security; regions; comparative analysis; regional development disparities